2013
DOI: 10.1371/journal.pone.0059679
|View full text |Cite
|
Sign up to set email alerts
|

PARP-1 and YY1 Are Important Novel Regulators of CXCL12 Gene Transcription in Rat Pancreatic Beta Cells

Abstract: Despite significant progress, the molecular mechanisms responsible for pancreatic beta cell depletion and development of diabetes remain poorly defined. At present, there is no preventive measure against diabetes. The positive impact of CXCL12 expression on the pancreatic beta cell prosurvival phenotype initiated this study. Our aim was to provide novel insight into the regulation of rat CXCL12 gene (Cxcl12) transcription. The roles of poly(ADP-ribose) polymerase-1 (PARP-1) and transcription factor Yin Yang 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 59 publications
(94 reference statements)
2
22
0
Order By: Relevance
“…Our previous results based on transfection experiments revealed that PARP‐1 plays a role in suppression of the Cxcl12 promoter . Findings presented herein strongly support an inhibitory role of PARP‐1 in the regulation of Cxcl12 gene expression.…”
Section: Discussionsupporting
confidence: 79%
“…Our previous results based on transfection experiments revealed that PARP‐1 plays a role in suppression of the Cxcl12 promoter . Findings presented herein strongly support an inhibitory role of PARP‐1 in the regulation of Cxcl12 gene expression.…”
Section: Discussionsupporting
confidence: 79%
“…The chemokine CXCL12 and its receptor, CXCR4, have been shown to mediate β -cell repair [ 28 ]. Immunohistochemical staining revealed the presence of CXCL12-positive cells only in diabetic islets and their increased presence in islets from Ld-treated rats.…”
Section: Resultsmentioning
confidence: 99%
“…Second, PARP1 inhibitors have been previously reported to play a critical role in regulating inflammatory response by modulating the expression of pro-inflammatory factors such as NF-κB, AP-1, IL-6 and downstream cytokines and chemokines [37,38,39,40]. Also, it has been shown that the overactivation of PARP1 promotes energy (NAD + /ATP) consumption and drives cell death, exacerbating the inflammation response [37,38,39,41]. PARP1 inhibitors thus may repress the NF-κB-mediated pro-inflammatory signals, and reduce energy failure and subsequent cell death induced by necrosis, thus providing a clinical potential for attenuating the cytokine storm and inflammatory response caused by SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 99%